Transesterifikasi In Situ Minyak Biji Pepaya Menjadi Metil Ester dengan Co-Solvent N-Heksana Menggunakan Microwave - Daryono, Elvianto Dwi; Sintoyo, Adi; Gunawan, Rendi Chandra (Jurnal Teknik Kimia dan Lingkungan, 2020)
In the dry weight of papaya seed oil contains up to 30%, so the potential to be used as raw material for biodiesel. Transesterification in situ is a simple step to produce biodiesel that is by eliminating extraction process and refining of oil so it can save on production costs and give satisfactory results. The reaction of one phase can be formed by adding a co-solvent to increase the solubility of oils. N-hexane is a co-solvent that is best because it is inexpensive, non-reactive and low boiling point (68°C) so that it can be separated by co-distillation with methanol. Microwave can propagate passed through the liquid so that the heating process will take place more effectively and the process of making biodiesel can be made shorter. In this study the variation of power used is 30%, 50% and 70% of 399 watts and the reaction time is 2,4,6,8 and 10 minutes. Results were analyzed by GC (Gas Chromatography). The optimum yield was 89.25% at 70% power and reaction time 8 minutes. The optimum yield has a density of 0.86 g / cm 3 and has an acid number of 0.28 mg KOH/g sample. These results have met the SNI 7182:2015.